2002
DOI: 10.1093/emboj/21.1.175
|View full text |Cite
|
Sign up to set email alerts
|

A role for RAD54B in homologous recombination in human cells

Abstract: In human somatic cells, homologous recombination is a rare event. To facilitate the targeted modi®cation of the genome for research and gene therapy applications, efforts should be directed toward understanding the molecular mechanisms of homologous recombination in human cells. Although human genes homologous to members of the RAD52 epistasis group in yeast have been identi®ed, no genes have been demonstrated to play a role in homologous recombination in human cells. Here, we report that RAD54B plays a critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
81
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 31 publications
6
81
0
Order By: Relevance
“…Although previous studies suggest that Rad54B plays roles in the HR and DNA repair processes 6,7 , we found a completely novel function of Rad54B; Rad54B suppressed the p53 levels and functions in the steady state independently of the activity of ATM (Fig. 1g,h and Supplementary Fig.…”
Section: Rad54b Suppresses the P53 Levels Independently Of Atmmentioning
confidence: 56%
See 2 more Smart Citations
“…Although previous studies suggest that Rad54B plays roles in the HR and DNA repair processes 6,7 , we found a completely novel function of Rad54B; Rad54B suppressed the p53 levels and functions in the steady state independently of the activity of ATM (Fig. 1g,h and Supplementary Fig.…”
Section: Rad54b Suppresses the P53 Levels Independently Of Atmmentioning
confidence: 56%
“…All media were supplemented with 10% fetal bovine serum. The RAD54B KO HCT116 cells were previously described 6 . MG132 (C2211) and cycloheximide (C4859) were obtained from Sigma-Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AtRAD54 is a putative homolog of SNF2/RAD54 subfamily that is involved in both DNA repair and transcriptional regulation. (65) AtRAD54 is activated in synthetic Arabidopsis auto-and allotetraploids but not in diploid parents and natural allotetraploids (A. suecica), (43) suggesting a role of DNA recombination and repair in the maintenance of genomic stability during early stages of polyploidy formation. Types of genomic and gene expression changes documented in the polyploids.…”
mentioning
confidence: 99%
“…Inactivation of the mouse RAD54 gene causes a marked sensitivity to DNA-damaging agents in embryonic stem cells, but somatic cells deleted for Rad54 show only a slight increase in radiosensitivity (43)(44)(45)(46). Inactivation of the RAD54B gene in a colon cancer cell line resulted in a severe reduction of targeted integration frequency, whereas sensitivity to DNA-damaging agents and sister chromatid exchange was not significantly affected (47). hRad54 protein colocalizes with hRad51 and BRCA1 in the nucleus (48,49), and significant colocalization of Rad54B with hRad51 and BRCA1 has also been observed (50).…”
mentioning
confidence: 99%